Quantitative stress radionuclide myocardial perfusion imaging can indicate significant coronary artery stenosis - T, Taerakul; A, Boonyaleepan; S, Sisai; T, Werawatganon (Biomedical Sciences and Clinical Medicine, 2019)
Objective The objective of this study was to evaluate the effectiveness of quantitative assessment of radionuclide myocardial perfusion imaging in indicating significant coronary artery stenosis. Methods Seven hundred and twenty patients with suspicion of coronary artery disease were retrospectively identified. All had undergone cardiac catheterization within a 6-month period after having had a one-day pharmacologic stress radionuclide myocardial perfusion scan. Important parameters analyzed included myocardial perfusion, wall motion, wall thickening severity scores of 3 coronary artery territories and left ventricular ejection fraction values. These parameters were subsequently compared with currently the gold standard for cardiac catheterization. Results Binary logistic regression analysis found that patients who had significant coronary artery stenosis had significantly higher values in all quantitative parameters (mean severity scores in myocardial perfusion, wall motion, wall thickening in most of the 3 coronary artery territories) than those in the non-significant group (p<0.05) with the exception of the wall motion severity score of the left circumflex artery. Similarly, patients with higher perfusion severity scores had a higher probability of significant coronary artery stenosis in all three coronary arteries. Conclusion Quantitative parameters obtained from stress radionuclide myocardial perfusion imaging can indicate significant coronary artery stenosis in all three main coronary arteries at a level comparable with that of cardiac catheterization which is currently the gold standard method but it is superior to cardiac catherization due to less invasive and less expensive. Higher perfusion severity scores indicate a higher probability of significant coronary artery stenosis.